1954
DOI: 10.1017/s0022029900007469
|View full text |Cite
|
Sign up to set email alerts
|

Section A. Physiology of dairy cattle: Part II. Physiology and Biochemistry of Rumination

Abstract: Since the time of the previous review in this series by the present author it has been increasingly realized that the ruminant's adaptation to its herbivorous diet is very far-reaching. The biochemical consequences of its need for coarse roughage are still being worked out and have necessitated a reassessment of the causes of bovine ketosis, of the function of lower fatty acids in its blood and of the reasons for its large requirement of cobalt. Recent work on all these three aspects of ruminant metabolism is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1955
1955
1967
1967

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 392 publications
0
3
0
Order By: Relevance
“…These concentrations are lower, and that in the kidney much lower, than those hitherto reported in hyperthyroid goats from this laboratory (Chanda & Owen, 1952). The known antithyroid action of vitamin A and carotene in a number of species (see books and reviews of Lindquist, 1938;Brody, 1945;Moore, 1957;Goodwin, 1952;Owen, 1941Owen, , 1947Owen, , 1951Owen, , 1954 and the anti-metabolic effect of vitamin A (Leutskii, I 961) make it reasonable to attribute the effect of carotene deprivation on the heart rate of the goat to the damping of the thyroid by dietary carotene. T h e interaction of the thyroid and vitamin A is complex (Chanda & Owen, 1952;Owen, 1962;Chanda, Clapham & Owen, 1955;Paul, Chanda & Chakraborty, 1962) and may be evident only when the intake of carotene is either too great or too small (Frape, Speer, Hayes & Catron, 1959).…”
Section: Abstracts Of Communications I963mentioning
confidence: 99%
“…These concentrations are lower, and that in the kidney much lower, than those hitherto reported in hyperthyroid goats from this laboratory (Chanda & Owen, 1952). The known antithyroid action of vitamin A and carotene in a number of species (see books and reviews of Lindquist, 1938;Brody, 1945;Moore, 1957;Goodwin, 1952;Owen, 1941Owen, , 1947Owen, , 1951Owen, , 1954 and the anti-metabolic effect of vitamin A (Leutskii, I 961) make it reasonable to attribute the effect of carotene deprivation on the heart rate of the goat to the damping of the thyroid by dietary carotene. T h e interaction of the thyroid and vitamin A is complex (Chanda & Owen, 1952;Owen, 1962;Chanda, Clapham & Owen, 1955;Paul, Chanda & Chakraborty, 1962) and may be evident only when the intake of carotene is either too great or too small (Frape, Speer, Hayes & Catron, 1959).…”
Section: Abstracts Of Communications I963mentioning
confidence: 99%
“…The liver reserves appeared to depend more on age than on carotene intake over a short period of time. Chanda, Clapham & Owen (97), considering vitamin A alcohol and ester separately, found that the ester and carotene in the milk fat reflected carotene intake, but that the level of the alcohol varied in the opposite direction, being highest when the carotene intake was low. They suggest that the increase in vitamin A alcohol is due to the transfer of liver reserves.…”
Section: (A) Vitamin a And Carotenementioning
confidence: 99%
“…This additional energy can also be supplied by adding fat, but the incorporation of fat into milk-replacement diets presents practical problems on the farm, though not on the Experiment Station that possesses a homogenizer. Owen (97) has reviewed the results obtained with a number of milk-replacement diets, further papers include (98), (99), (ioo), (ioi), (102) and (103). Calf rearing has undoubtedly been greatly helped by the use of antibiotic supplements, and such an addition is commonly made to the feed of calves in the United States, and the role of antibiotics in ruminant nutrition is excellently reviewed in (104) and (105).…”
Section: Milk and Milk Products For The Pre-ruminant Calfmentioning
confidence: 99%